Organizational Performance through Socialization and Role of Social Media: Empirical Evidence from Manufacturing Companies of Pakistan - Memon, Javed Ahmed; Aziz , Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Social media applications including Facebook, WhatsApp, and others, are essential tools for today’s businesses and these are becoming critical sources of information. This study has identified five critical factors for measuring the impact social media on organizational performance; information, knowledge, role clarity, self efficacy and support system. This study is based on primary data analysis and conducted through a self administered close-ended questionnaire, designed and distributed among 500 employees of different manufacturing companies of Pakistan through random sampling. The structural equation model has been applied by using PLS smart and SPSS packages. Our study finds that social media applications have a significant impact on gaining information and knowledge, understanding the role and developing a support system. In contrast, social media applications have no impact on clarifying goals and targets and self-efficacy. It is recommended that organizations should encourage the use of social media applications in the organization in order to promote socialization among the employees.